Pioglitazone - A Bullet for Many Targets! - M, Deepalakshmi; Atluri, Haritha; KP, Arun (Indian Journal of Pharmacy Practice)
Obesity and aging has resulted ever increasing incidence of type 2 diabetes in many developing countries including India. Among the various classes of anti-diabetic agents including being used in the clinics, thiazolidinediones (TZDs) comprise important class which is Peroxisome Proliferator-Activated Receptor Gamma (PPARG) agonists. This article reviews the Pharmacology of Pioglitazone beyond its anti-diabetic effect. Thorough literature search was done including e-resources to understand the clinical evidences for the anti-diabetic and extra anti diabetic activities of Pioglitazone. Pioglitazone is known to successfully control the HbA1c levels not only in many patients with Type 2 diabetes but, also in pre-diabetic subjects. We generally use lower doses of Pioglitazone (about 30 mg) in India and so it will take longer time to reach the cumulative dose, and if use the dose of 7.5 mg, it would take even longer time close to 10 years. Thus, low dose Pioglitazone has been very widely used due to its efficacy and lower frequency of side effects including weight gain and fluid retention. It can be concluded that the literature evidences suggest that Pioglitazone has acceptable safety profile, many extra anti diabetic effects including cardiovascular and pleotropic effects apart from its use in Type 2 diabetes patients and pre-diabetic individuals.
Keywords: Pioglitazone; PPARgamma agonists; Type 2 diabetes; Extra anti diabetic effect.